2020
DOI: 10.3348/kjr.2020.0567
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Volumetric Quantitative CT Analysis in Patients with COVID-19: A Multicenter Study in Daegu, Korea

Abstract: Objective Lung segmentation using volumetric quantitative computed tomography (CT) analysis may help predict outcomes of patients with coronavirus disease (COVID-19). The aim of this study was to investigate the relationship between CT volumetric quantitative analysis and prognosis in patients with COVID-19. Materials and Methods CT images from patients diagnosed with COVID-19 from February 18 to April 15, 2020 were retrospectively analyzed. CT with a negative finding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…These findings were consistent with other previous studies that evaluated risk factors associated with acute respiratory distress syndrome in patients with COVID-19. 11 13 26 27 Elevated CRP and procalcitonin levels in the severe group may have been associated with cytokine storms triggered by viral invasion or due to the presence of co-infections, as reported in a recent study. 28 …”
Section: Discussionsupporting
confidence: 51%
“…These findings were consistent with other previous studies that evaluated risk factors associated with acute respiratory distress syndrome in patients with COVID-19. 11 13 26 27 Elevated CRP and procalcitonin levels in the severe group may have been associated with cytokine storms triggered by viral invasion or due to the presence of co-infections, as reported in a recent study. 28 …”
Section: Discussionsupporting
confidence: 51%
“…This means that in severely ill patients, after reaching a particular critical value, further progression of the disease will not influence the growth of inflammatory parameters, D-dimers, LDH or the decrease in the lymphocyte count. Park B. et al revealed that CRP in the mild pneumonia group and normally aerated lung proportion volume in the severe pneumonia group were independently associated with critical event-free survival in patients with COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While viral testing remains the only specific method of diagnosis [ 5 ], CT plays a role in the workup of suspected pulmonary manifestations of COVID-19 and associated complications. There is growing evidence that radiographic [ 6 ] and chest CT [ 7 8 9 10 11 12 13 14 15 ] features are associated with disease severity in COVID-19 based on (semi)-manual assessment and visual scoring of pulmonary parameters. This study intends to build on these approaches and expand them in three aspects: First, by introducing a fully automated and user-independent evaluation method, which is especially relevant in pandemic period with heavy workloads on healthcare providers.…”
Section: Introductionmentioning
confidence: 99%